Users' satisfaction on library performance in Universiti Putra Malaysia Medical Library: a case study / Elina Malek - Malek, Elina (2009)
This study investigates users' satisfactions on library performance in University Putra Malaysia (UPM) Medical Library, Serdang. The main purpose of this study is to identify users' satisfactions towards services, facilities, library staff and the collections provided by University Putra Malaysia (UPM) Medical Library. The data collection instrument was a self-administered questionnaire. One-hundred and fifty questionnaires were distributed randomly to the library users within two weeks on March 2009. The questionnaire used in this study was adapted from a previous study on users' satisfactions survey in an academic library (Heriot Watt University Users' Satisfactions Survey, 2000; and Roslah & Zainab, 2007). The findings indicate that most of the students are satisfied with the library services, facilities, staffs and collections. It is expected that findings of this study will be useful for these libraries in re-orienting their resources, services and facilities to synchronize them with the information needs of their students or library users. The study may also contribute to the existing body of knowledge on user satisfaction and library effectiveness especially in academic libraries in Malaysia.